Making comparisons in equality law : within gender, age and conflicts / Robin Allen. - Allen, Robin (Barrister) (Hamlyn Lectures ;, 2020)
This book seeks to rebalance the relationship between comparison and justification to achieve more effective equality and non-discrimination law. As one of the most distinguished equality lawyers of his generation, having appeared in over 40 cases in the House of Lords and the Supreme Court and many leading cases in the Court of Justice, Robin Allen QC is well placed to explore this critical issue. He shows how the principle of equality is nothing if not founded on apt comparisons. By examining the changing way men and women's work has been compared over the last 100 years he shows the importance of understanding the framework for comparison. With these insights, he addresses contemporary problems of age discrimination and conflict of equality rights.